Pengaruh Tekanan Stakeholders dan Board Gender Diversity pada Kualitas Laporan Keberlanjutan (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Rahmawati, Erika; Sudana, I Putu (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of stakeholder pressure proxied by environmental pressure, consumer pressure, employee pressure, and shareholder pressure, as well as board gender diversity on the quality of sustainability reports. This study uses a quantitative approach with secondary data analysis from annual reports and sustainability reports of non-financial companies listed on the Indonesia Stock Exchange (IDX) using the 2018-2022 research period. This study uses panel data regression analysis. The sampling method uses a non-probability sampling method with a purposive sampling technique and 514 observations were obtained. The results of this study reveal that simultaneously there is a positive and significant influence between the variables of environmental pressure, consumer pressure, employee pressure, shareholder pressure and board gender diversity on the quality of sustainability reports, but partially there is no significant influence of employee and shareholder pressure variables on the quality of sustainability reports of non-financial companies listed on the IDX for the period 2018-2022.